Effects of music intervention on golf-specific skill performance of golfers under mental fatigue: Protocol for a randomized controlled trial - Xiaoyang Pan; Kim Geok Soh; Wan Marzuki Wan Jaafar; He Sun; Guoyao Zhang (PLoS ONE, 2025)
Given that golf tournaments last approximately five hours without an intermission, mental fatigue has become a critical factor affecting performance. Although research has shown that music intervention can effectively alleviate mental fatigue, this method has yet to be applied in golf. Therefore, this study aims to evaluate the effects of music intervention on golf-specific skill performance under mental fatigue. This study adopts a randomized, controlled, partially-blind design, including three groups. The MF-Mu group undergoes a mental fatigue induction task followed by a music intervention. The MF-nMu group completes the same mental fatigue task but does not receive the music intervention. The CON group serves as the control and receives neither the mental fatigue task nor the music intervention. Controlled variables include immersion tendency, sport anxiety, attention, motivation, and perceived exertion. Primary outcome measures include mental fatigue, driving shot, iron shot, chipping shot, and putting performance. Performance measures include accuracy and shot quality. In this study protocol, the use of smartphones for music intervention enhances its portability, allowing the intervention to be initiated or terminated at any time, increasing its flexibility and acceptability. Moreover, briefly listening to music during non-striking moments complies with golf regulations, making this study highly practical. It provides an effective strategy for golfers to manage mental fatigue in competitive environments. Trial registration ClinicalTrials.gov NCT06952283